Effect of emotional regulation on performance of shooters during competition: An ecological momentary assessment study - Zhou Lulu; Liu Huimin; Su Hua (PLoS ONE, 2025)
Objective The purpose of this study was to examine the effect of emotion regulation on shooting performance in shooting athletes. Method Ecological momentary assessment was used to track and examine the dynamic relationship between pre-competition and in-competition emotions, emotion regulation strategy selection and use, and shooting performance in 57 shooting athletes. Results Female athletes used more regulation strategies than male athletes and had lower mean shooting scores when using disengagement strategies and lower good ten-ring percentages when using engagement strategies compared to male athletes. Elite athletes had a higher percentage of ten-ring scores when using engagement strategies than did first-level athletes, but a lower percentage of ten-ring scores when using disengagement strategies. The use of emotion regulation strategies and situational demands were not strongly related. Athletes had low flexibility in emotion regulation and were better at using disengagement strategies, but disengagement strategies were not beneficial for shooting performance. Conclusions First-level athletes have a higher contextual demand for emotion regulation and tend to use disengagement strategies more frequently to regulate emotions. Elite-level athletes have higher average ring values and ten-ring ratios when using engagement strategies under lower contextual demand and using disengagement strategies under higher contextual demand. Enhancing flexible emotional regulation training that improves situation-strategy fit may be beneficial for enhancing sports performance.